Seven empty houses - Schweblin, Samanta, 1978- (Riverhead Books, 2022)
"The seven houses in these seven stories are empty. Some are devoid of love or life or furniture, of people or the truth or of memories. But in Samanta Schweblin's tense, visionary tales, something always creeps back in: a ghost, a fight, trespassers, a list of things to do before you die, a child's first encounter with a dark choice or the fallibility of parents. This was the collection that established Samanta Schweblin at the forefront of a new generation of Latin American writers. And now in English it will push her cult status to new heights. Seven Empty Houses is an entrypoint into a fiercely original mind, and a slingshot into Schweblin's destablizing, exhilarating literary world. In each story, the twists and turns will unnerve and surprise: Schweblin never takes the expected path and instead digs under the skin and reveals uncomfortable truths about our sense of home, of belonging, and of the fragility of our connections with others. This is a masterwork from one of our most brilliant writers"--